Carta de J.J. Henna a Roberto H. Todd - Todd, Roberto H.; Henna, J. J. (My University, 1898)
Carta de J. J. Henna a Roberto H. Todd agradeciendole la canasta de frutas que le dio.
Keywords: Henna, José Julio, 1848-1924; Henna, J. J.--Correspondence.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.; Henna, J. J.--Correspondencia.